Numerical Simulation of Imported Sediment in a Stilling Basin - Wang, Rui; Li, Peng; Li, Zhanbin; Han, Jianchun; Zhu, Yubin (Frontiers in Earth Science, 2021)
Sediment buildup at the bottom of a stilling basin can result in premature drainage of spillway structures and can even lead to dam failure in severe cases. Such failures pose ecological and human safety hazards to downstream areas. To evaluate the sudden discharge and potential dam failure associated with sediment buildup, we developed a two-dimensional two-phase flow simulation model built on a particle-based force balance equation. We compared the flow patterns and energy dissipation effects in the stilling basin at different inlet flows (2, 3, 4.5, and 6.75 m2/s), and the subsequent bottom deposition was compared across different sand discharge mass flow rates (0.1, 0.2, and 0.3 kg/s). The results show that the turbulent energy increased with the increasing inlet unit width flow rate. When more vortices were generated and the flow velocity was reduced significantly, the energy dissipation was more effective. The sediment deposition at the bottom of the stilling basin gradually increased with the decrease of inlet unit width flow and the decrease of the sediment mass flow rate. Meanwhile, at a fixed inlet shape, the change in inlet unit width flow had little effect on the maximum sedimentation height at the bottom of the basin. In addition, the average deposition rate at the bottom of the stilling basin was positively correlated with the inlet sedimentation concentration, and the correlation coefficient could be as high as 0.97. In this two-phase flow method, the error of the simulated value over the theoretical value was less than 10%. This simulation of sediment deposition at the bottom of the stilling basin provides a practical reference for dam managers.